The Tripartite Game Model for Electricity Pricing in Consideration of the Power Quality - Tianlei Zang; Yueping Xiang; Jianwei Yang (Energies, 2017)
Under the Energy Internet concept the distribution and management of resources in the electricity market have been gradually transiting from a centralized pattern to a decentralized pattern. Correspondingly, the methodological model for the analysis of economic behaviors needs to be upgraded too. Based on the idea of non-cooperative game theory, this paper puts forward a tripartite game model for electricity pricing in consideration of the power quality, which is applicable to the electricity market under the Energy Internet with distributed generation, including the State Grid Corporation of China (SGCC), generating companies (GENCOs) and the marketers which correspond to the regional power-retailing companies. Then, the sequential quadratic programming based on the quasi-Newton method is given to solve the game model. Finally, four sets of tests with different game factors are carried out to verify the validity and feasibility of the proposed model and algorithm. The SGCC price, the cost and the number of GENCOs and the cross-regional environment are considered in each test, respectively. The results show that this model can adapt well to the various conditions.